2019
DOI: 10.1186/s12879-019-3713-0
|View full text |Cite
|
Sign up to set email alerts
|

Health providers’ experiences, perceptions and readiness to provide HIV services to men who have sex with men and female sex workers in Uganda – a qualitative study

Abstract: Background Access to HIV services among men who have sex with men (MSM) and female sex workers (FSWs) remains suboptimal globally. While the reasons for this dismal performance have been documented, limited evidence exists on the experiences, perceptions and readiness of health providers to provide HIV services to MSM and FSWs. Methods This analysis uses data collected from 48 key informants (health providers in public and private health facilities) as part of a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
(55 reference statements)
2
24
0
Order By: Relevance
“…Across most of Africa, key populations face discrimination, judgements, and negative attitudes from health care workers. These factors act as barriers in accessing healthcare services by lesbian, gay, bisexual and transgender (LGBT) populations [27,38,39]. Furthermore, same sex relationships in sub-Saharan Africa are heavily stigmatized and criminalized in many countries in the continent [40,41].…”
Section: Sexual Health Care Deliverymentioning
confidence: 99%
“…Across most of Africa, key populations face discrimination, judgements, and negative attitudes from health care workers. These factors act as barriers in accessing healthcare services by lesbian, gay, bisexual and transgender (LGBT) populations [27,38,39]. Furthermore, same sex relationships in sub-Saharan Africa are heavily stigmatized and criminalized in many countries in the continent [40,41].…”
Section: Sexual Health Care Deliverymentioning
confidence: 99%
“…HIV testing is the entry point to HIV care; increasing testing coverage is a key step to reaching the first UNAIDS 90-90-90 target, i.e., 90% of people living with HIV knowing their HIV status. However, testing uptake is still low among MSM despite efforts to scale up prevention services for key populations (KP) in Uganda [5][6][7][8]. A recent bio-behavioral survey of Ugandan MSM found that 35% had never tested for HIV [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have documented that a lack of specific skills can affect continuum of care for MSM. 36 , 37 , 40 In contrast, other studies showed that health care providers trained in MSM specificity provide better holistic care while considering the social aspects of their lives. 30 It follows that training of health care providers will lead to skill improvement for quality of healthcare; however, efforts to shift attitudes have to consider the cultural components of the society.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been proved that negative attitudes of health care providers have shifted due to the implementation of educational interventions; one of the recommendations made by the participants. 37 …”
Section: Discussionmentioning
confidence: 99%